Effects of drum drying on physical and antioxidant properties of riceberry flour - Wiriyawattana, Porntip; Suwonsichon, Suntaree; Suwonsichon, Thongchai (Agriculture and Natural Resources, 2018)
The effects of drum drying on the physical and antioxidant properties of pregelatinzed riceberry flour were investigated. The drum drying temperature was varied (110°C, 120°C and 130°C) and unheated riceberry flour was used as the control. The results showed that all pregelatinized riceberry flour samples had lower (p <0.05) L* value, but higher (p < 0.05) a* and b* values than the control. Thewater absorption index and swelling power of all pregelatinized riceberry flour samples were also significantly (p < 0.05) higher than those of the control. The results from rapid visco analysis indicated that the pasting time, pasting temperature, peak viscosity, trough viscosity, final viscosity and set back of riceberry flour decreased (p < 0.05) after drum drying. Moreover, the total phenolic content and antioxidant capacity, as measured using 2,2-diphenylpicrylhydrazyl and 2,2'azinobis (3-ethylbenzothiozoline-6-sulfonic acid) disodium salt radical assays, respectively, also decreased (p <0.05) after drum drying. Such changes were more evident with increased drum drying temperature in the range 110-130°C. In addition, increasing the drum drying temperature led to poorer stability to withstand the thermal treatment and stress than in pregelatinized riceberry flour. The results suggested that special attention should be given to the drum drying temperature as it affects not only the physical but also the antioxidant properties of the pregelatinized riceberry flour. Pregelatinized riceberry flour produced using drum drying at 110°C could be applied to formulate an instant soup product because it had high values for water absorption capacity, total phenolic content and antioxidant activity and was completely gelatinized and stable against thermal treatment and stress.